P3.217 International Comparison of Recent Trends in the Rates of HIV Diagnoses Among Men Who Have Sex with Men (MSM). (13th July 2013) - Foster, T; Dickson, N; Saxton, P
Abstract : Background: After a rise in the early 2000s in the number of new HIV diagnoses among MSM in New Zealand, also witnessed in many developed countries, in 2011 the number dropped by 34% compared to 2010. To assess relative progress on control we compare trends in HIV diagnosis rates among MSM in developed countries with similarly mature epidemics. Methods: We obtained data on annual HIV diagnoses among MSM between 2003–2011 from 17 developed countries (Australia, Belgium, Canada, Denmark, Finland, France, Iceland, Ireland, Netherlands, New Zealand, Norway, Spain, Sweden, Switzerland, Germany, UK, US). We reallocated those with unknown means of infection according to the countries' pattern of known causes, and used countries' adjustment for delayed reporting where available. The diagnosis rate was derived using the population of men aged 15–64. Results: New Zealand has low rates compared to most countries of Western Europe, North America and Australia, and are comparable with those of Scandinavia All counties except New Zealand, Iceland and Canada, experienced a slight overall rise in diagnosis rates in the period 2003–2011 Over the past four years there has been a: Slight trend upwards in UK, Belgium, France, Australia, Ireland No clear trend in Spain, Canada, Germany, Denmark, Norway Slight trend downwards in New Zealand, the Netherlands, Sweden, Finland, and possibly Iceland Clear trend downwards in Switzerland. Conclusions: New Zealand has a low rate of HIV diagnoses, relative to many other developed countries. Our drop in 2011 HIV is encouraging but not unique. Limitations of this study are that the data are of diagnosis not infection rates, are influenced by patterns of testing, immigration and emigration, and dual modes of transmission, and the proportion who are MSM may vary between countries. Factors relating to recent trends should be explored.